Utilization Edugames Baamboozle as an Evaluation Media for the Biology Cognitive Abilities of Class 14 Bone High School Students - Nurdiana, Nurdiana; Wahyuni, Sri; Asmah, Sitti (Magister Pendidikan Biologi, Universitas Negeri Medan, 2024)
This research aims to find out how the Edugames baamboozle media is used as an evaluation medium for the biology cognitive abilities of class X students at SMAN 14 Bone. The research used is quantitative research with the Pre-Experimental Design type of research with the One Group Pre-test and Post-test Design type. The data collection technique used in this research is giving a pre-test and post-test in the form of multiple choice and documentation. The results of inferential analysis using three tests, namely normality test, homogeneity test and hypothesis test, are known from the results of normality data analysis using one Kolmogrov-Smirnov test, pre-test 0.83 Ëƒ 0.05 and post-test 0.37 > 0.05 (normal ). The homogeneity test using Levene Statistics shows 0.32 Ëƒ 0.05 (homogeneous) and based on the t test using the Paired-test the significant rate used is Î± = 0.05. The data obtained is significant (0.000) Ë‚ = 0.05, thus H0 is rejected and there was acceptance of H1 which showed that there was effectiveness before the treatment was given and after the treatment using the Edugames baamboozle media. Based on research conducted at SMAN 14 Bone, the average pre-test score was 39.7, while the average post-test score was 85.0. The post-test score was higher than the pre-test score. It can be concluded that through the Edugames baamboozle media it has an influence on the Biology cognitive abilities of class XI students at SMAN 14 Bone and they provide a positive response to this learning media.